2020
DOI: 10.1093/neuros/nyaa051
|View full text |Cite
|
Sign up to set email alerts
|

Case Series: Unilateral Amygdala Ablation Ameliorates Post-Traumatic Stress Disorder Symptoms and Biomarkers

Abstract: BACKGROUND Post-traumatic stress disorder is a severe psychobiological disorder associated with hyperactivity of the amygdala, particularly on the right side. Highly selective laser ablation of the amygdalohippocampal complex is an effective neurosurgical treatment for medically refractory medial temporal lobe epilepsy that minimizes neurocognitive deficits relative to traditional open surgery. OBJECTIVE To examine the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Studies investigating the neural bases of psychiatric treatment response have repeatedly reported that reductions in depressive, anxiety, obsessive-compulsive, and posttraumatic stress symptoms occur concomitantly with a normalization of amygdala activity ( 17 , 37 , 41 44 ). Associations between clinical improvement and modified amygdala functioning have been observed following treatment with psychotropics, cognitive behavioral therapy, electroconvulsive therapy, and surgical interventions, convergently suggesting that neuromodulation of the amygdala may facilitate efficacious reductions in transdiagnostic psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the neural bases of psychiatric treatment response have repeatedly reported that reductions in depressive, anxiety, obsessive-compulsive, and posttraumatic stress symptoms occur concomitantly with a normalization of amygdala activity ( 17 , 37 , 41 44 ). Associations between clinical improvement and modified amygdala functioning have been observed following treatment with psychotropics, cognitive behavioral therapy, electroconvulsive therapy, and surgical interventions, convergently suggesting that neuromodulation of the amygdala may facilitate efficacious reductions in transdiagnostic psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the FPCN has functionally relevant subnetworks that differentially relate to PTSD. The LN B subnetwork-composed of temporal pole regions that are infrequently implicated in the PTSD literature (although see [46,47]) has shown connectivity to amygdala and hippocampal regions [48] which are more commonly associated with PTSD [5,49]. These temporal pole regions have been associated with social and emotional processing [21][22][23] and damage to the temporal pole can lead to unstable mood [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to people without PTSD, people with PTSD show greater amygdala activation when viewing negative emotional faces and scenes or other trauma-related stimuli 26,27 . Furthermore, surgical ablation of amygdala is associated with remediation of PTS symptoms, suggesting its central role in the pathophysiology of the disorder 28 . In our study, children who readily differentiate fearful from neutral stimuli and typically show greater amygdala activation in response to fearful faces were at reduced risk for storm-related PTS ( B = −1.6, t (280) = −3.25, p = 0.001, 95% Confidence Interval = −2.57 to −0.64, β = −0.14).…”
Section: Neural Vulnerability Moderates Media Effects On Posttraumatimentioning
confidence: 99%
“…For example, compared to people without PTSD, people with PTSD show greater amygdala activation when viewing negative emotional faces and scenes or other trauma-related stimuli 32,33 . More directly, surgical ablation of amygdala is associated with remediation of PTS symptoms, suggesting its central role in the pathophysiology of the disorder 34 .…”
Section: Neural Vulnerability Moderates Effects Of Irma Experiences and Anticipatory Media Exposure On Posttraumatic Stressmentioning
confidence: 99%